Identifying and prioritizing the advantages of implementing blockchain technology in public-private enterprises - Forozandeh, Mohammad (goodwood publishing, 2025)
Purpose: Identifying and prioritizing the benefits of implementing blockchain technology in public-private enterprises. Research Methodology: A comprehensive literature review on this topic revealed a variety of benefits associated with the implementation of blockchain technology. These identified benefits were then presented to experts for prioritization through the use of the DEMATEL questionnaire, leading to the development of the DANP decision matrix. Results: The benefits were systematically ranked, resulting in the prioritization of tracking, security, and sustainability. Regarding the importance of the identified benefits, the experts ranked